The Role of Civic Education and Sharia Business in Shaping a Generation of Young Entrepreneurs with Integrity in the Digital Era - Abidatul Maknun; Ika Wulandari; Ayunda Hanum Firdausi; Siti Aisyah; Erlin Wijaya (Jurnal Ilmu Pendidikan dan Humaniora, 2026)
This study aims to examine the interconnection between the values of Civic Education (PKn) and the principles of Sharia economics in the development of young entrepreneurs in the digital era, where digital transformation opens broad entrepreneurial opportunities through online platforms while simultaneously presenting challenges such as unhealthy competition, lack of transparency, and declining integrity in business practices. Using a literature review method, this research analyzes various theoretical sources related to Civic Education values, civic ethics, Sharia economic principles, and digital entrepreneurship. The findings indicate that Civic Education values—such as responsibility, honesty, legal awareness, and social concern—play a significant role in shaping the ethical character of young entrepreneurs, while Sharia economic principles, including justice, halal orientation, and the prohibition of gharar, reinforce fair, transparent, and accountable digital business practices. The integration of these two frameworks provides a comprehensive ethical foundation that supports the development of young entrepreneurs who are not only economically capable but also possess strong moral character and a commitment to the public good, thereby contributing to a sustainable and ethical digital entrepreneurship ecosystem